PENGARUH ATRIBUT PRODUK, CELEBRITY ENDORSER DAN WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN PRODUK KOSMETIK WARDAH (Studi Kasus pada Mahasiswi S-1 FISIP UNDIP) - Sari, Dwi Oktaviana; Widiartanto, Widiartanto; Listyorini, Sari (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2015)
Nowdays, there are many cosmetic products have emerged and circulated in Indonesia. It makes many choices for the consumer to decide on the purchase of cosmetics. There are several factors that influence the consumer to purchase decisions. Based on the existing problems in this study that there is still a decrease in sales growth of the product of Wardah cosmetics per month and the results of the pre-survey interviews with 10 respondents indicated that the product attributes in terms of product packaging is not good enough, lacking of the respondents confidence towards the celebrity endorser, and there is still the negative word of mouth about Wardah cosmetic products. The purpose of this study is know the effect of product attribute, celebrity endorser and word of mouth towards purchasing decisions Wardah cosmetic products. The type of research is explanatory research. The number of sample were taken from 100 respondents with sampling purposive technique. In collecting data, the writer uses questioner and interview. In analyzing the data, the writer used method of crosstab, correlation, determination, simple linear regression, multiple linear regression, test of t and f. The results of the analysis showed that there is positive effect and significant between product attributes, celebrity endorser and word of mouth towards purchasing decision Wardah cosmetic products either partially or simultaneously. It is suggested that to increase the purchasing decision of the Wardah cosmetic products, the company should be able to make interesting packaging and the beauty advisors should be more interactive and communicative to the consumer, helding a workshop and tutorial make up along with celebrity endorser, and approaching the woman such as hijabers community so that in the future, it can be can the leaders opinion to increase word of mouth.